2012
DOI: 10.1111/j.1399-6576.2012.02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac–tramadol vs. diclofenac–acetaminophen combinations for pain relief after caesarean section

Abstract: Both diclofenac-tramadol and diclofenac-acetaminophen combinations can achieve satisfactory post-operative pain control in women undergoing caesarean section. The diclofenac-tramadol combination was overall more efficacious but associated with higher incidence of post-operative nausea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 11 publications
6
36
2
Order By: Relevance
“…The diclofenac + tramadol combination was overall more efficacious but associated with higher incidence of post-operative nausea. 28 In our study the incidence of nausea was 3% in tramadol group but increased to 10% in the tramadol + NSAID group (tramadol + piroxicam).…”
Section: Discussionmentioning
confidence: 40%
“…The diclofenac + tramadol combination was overall more efficacious but associated with higher incidence of post-operative nausea. 28 In our study the incidence of nausea was 3% in tramadol group but increased to 10% in the tramadol + NSAID group (tramadol + piroxicam).…”
Section: Discussionmentioning
confidence: 40%
“…In the study conducted by Mitra et al [18], tramadol-diclofenac was associated with comparable side effects with tramadolparacetamol and higher incidence of post-operative nausea. Use of rescue analgesic intake was similar between two groups (P = 0.872).…”
Section: Daymentioning
confidence: 88%
“…Mitra et al [18] have showed that diclofenac-tramadol and diclofenacparacetamol combinations are effective in providing postoperative pain control after caesarean section. The investigators demonstrated that the overall efficacy of diclofenac-tramadol combination is better than diclofenac-paracetamol.…”
Section: Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Although multimodal analgesic combinations are well accepted, finding the right combination remains the key challenge. 9 We explored multimodal approach to pain relief after cesarean section using two different drugs with different routes of administration and mechanisms of action. We therefore compared the analgesic and side effect profile of intramuscular pentazocine alone or in combination with piroxicam.…”
Section: Introductionmentioning
confidence: 99%